Faktor yang Berhubungan dengan Penerimaan Vaksin HPV - Sangadji, Namira Wadjir; Ayu, Ira Marti; Veronika, Erna (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2024)
ABSTRACT Background of Study: Cervical cancer prevention will be more effective if accompanied by specific protective measures such as HPV immunization. A preliminary study conducted on May 28, 2022, on ten seventh grade students of Ma'Arif Sukaraja Junior High School found that 30% of parents refused the vaccine due to concerns related to its permissibility. The aim of this study was to identify factors associated with HPV vaccine acceptance by parents at Ma'Arif Sukaraja Junior High School in 2022. Methods: The research design used was analytic observational with a cross-sectional design. The population in this study consisted of all parents of Ma'Arif Sukaraja Junior High School students, totaling 58 people. The study used the total sampling method with all 58 individuals as samples. Data collection was done by distributing questionnaires to students, which were then taken home to be filled in by their parents. Results: About 46.66% of parents refused the HPV vaccine, with the most common reason for refusal being distrust of the vaccine (42.66%). The chi-square test showed a significant association between poor parental knowledge of HPV vaccine (PR: 3.04; p value: 0.01) and history of cancer infection (PR: 0.02; p value: 0.01). Logistic regression analysis showed that the factor that most influenced HPV vaccine acceptance at Ma'Arif Sukaraja Junior High School in 2022 was poor parental knowledge about the HPV vaccine (PR: 12.98; p value: 0.01). Conclusion: The most influential variable in HPV vaccine acceptance at Ma'Arif Sukaraja Junior High School in 2022 is poor parental knowledge about the HPV vaccine. Keywords: HPV, Vaccine Acceptance, Parents